OSTEOARTHRITIS IN PATIENTS WITH DIFFERENT TYPES POLYMORPHISM RECEPTOR GENE VITAMIN D - Терешкін, К.І. (World of Medicine and Biology, 2016)
As a result of in-depth clinical examination of 96 patients it was found that prevailed patients with homozygous genotype BB, the frequency of which found significantly higher than the homozygous genotype and genotype bb Bb (respectively (45,8 ± 5,1)%, (19,8 ± 4,1)% and (34,4 ± 4,8)%, p
Keywords: gene polymorphism of the D vitamin receptor; osteoarthritis; obesity; apelin